Tinjauan Yuridis Kekuatan Hukum Sertifikat Tanah Elektronik Berdasarkan Peraturan Menteri Agraria Dan Tata Ruang Nomor 1 Tahun 2021 - Risti Dwi Ramasari; Shella, Shella Aniscasary (Jurnal Hukum dan Etika Kesehatan, 2022)
Land certificates are documents of proof of land ownership rights as the final product of the land registration process. The purpose of the study is to provide knowledge and understanding of the legal power of electronic land certificates and provide knowledge and understanding of the position of electronic land certificates in land registration law in Indonesia. research method using normative juridical. Electronic certificates are included in authentic deeds even if they are in electronic form. Electronic certificate contains Electronic signature. In the rule of law in Indonesia, there has never been a definition of the word signature, which actually has two basic functions as a sign of the identity of the signing and the sign of approval of the signing of the obligations attached to the deed. Electronic land certificates have a position as strong evidence in land registration law in Indonesia, land registration procedures to obtain electronic certificates must refer to the Minister of ATR/BPN Regulation Number 1 of 2021 concerning Electronic Certificates.